Break Even Point Analysis For Sales Planning At PT Ultrajaya Milk Industry And Trading Company Tbk - Kartika Septiary Pratiwi Musa; Haliah; Darmawati (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the application of Break Even Point (BEP) analysis as a strategic instrument for sales planning and profit management at PT Ultrajaya Milk Industry & Trading Company, Tbk during the 2022–2024 period. The study seeks to evaluate the company's operational efficiency through contribution margin performance, break-even trends, and sales target achievement in the post-pandemic business environment. A quantitative descriptive approach was employed using secondary data obtained from PT Ultrajaya’s independently audited annual financial statements for 2022–2024. The analysis involved cost classification, contribution margin (CM) calculation, contribution margin ratio (CMR) analysis, BEP determination in monetary terms, and sales target planning based on Cost-Volume-Profit principles. The results indicate a consistent increase in net sales from IDR 7.456 trillion in 2022 to IDR 8.874 trillion in 2024. The contribution margin ratio improved substantially from 19.65% to 34.05%, reflecting enhanced operational efficiency and stronger profitability. The break-even point declined from IDR 5.874 trillion in 2022 to IDR 4.620 trillion in 2024, demonstrating a wider margin of safety. Furthermore, actual sales consistently exceeded both the calculated BEP and planned sales targets throughout the study period. The findings suggest that BEP analysis provides valuable managerial information for establishing realistic sales targets, monitoring cost efficiency, evaluating profit performance, and supporting strategic decision-making in manufacturing companies facing dynamic market conditions. This study contributes to the accounting and management literature by integrating contribution margin analysis, break-even trend evaluation, and sales target planning within a single analytical framework. It provides empirical evidence from a large publicly listed Indonesian manufacturing company during the post-pandemic recovery period, an area that remains relatively underexplored in previous BEP studies.